2021
DOI: 10.3389/fmicb.2021.739521
|View full text |Cite
|
Sign up to set email alerts
|

The Costs and Benefits of Two Secondary Symbionts in a Whitefly Host Shape Their Differential Prevalence in the Field

Abstract: Insects commonly harbor maternally inherited intracellular symbionts in nature, and the microbial partners often exert influence on host reproduction and fitness to promote their prevalence. Here, we investigated composition of symbionts and their biological effects in the invasive Bemisia tabaci MED species of a whitefly complex. Our field surveys revealed that populations of the MED whitefly, in addition to the primary symbiont Portiera, mainly contain two secondary symbionts Hamiltonella, which is nearly fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 75 publications
3
6
0
Order By: Relevance
“…was 92.3% in MED, 71.6% in MEAM1, 0.13% in Asia I, and 3.57% in China 1. The results regarding the infection frequency of endosymbionts among cryptic species were consistent with previous reports [ 17 , 61 , 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…was 92.3% in MED, 71.6% in MEAM1, 0.13% in Asia I, and 3.57% in China 1. The results regarding the infection frequency of endosymbionts among cryptic species were consistent with previous reports [ 17 , 61 , 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data show that Cardinium infection frequency was not uniform in B. tabaci MED populations across China according to 2 field investigations completed during 2012 and 2021, with a higher prevalence observed in South China and a lower prevalence recorded in North China. These findings were consistent with previous field surveys (Pan et al, 2012;Shan & Liu, 2021). A similar phenomenon was found in another cryptic species (B. tabaci Middle East Asia Minor 1) with its facultative symbiont Rickettsia.…”
Section: Discussionsupporting
confidence: 92%
“…However, previous work has demonstrated that Cardinium infection confers significant fitness costs to B. tabaci MED, including weaker competitive ability, reductions in fecundity and egg survival rate, and delay in development (Fang et al. , 2014; Shan & Liu, 2021). It suggests a complex nature of the close symbiotic associations between Cardinium and the host whitefly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. marcescens presence in insect midguts was detected using specific PCR primers targeting the bacterium's 16S rRNA gene with the forward primer Ser16S-F (5'-CCTTC GGG TTG TA A AGCACT-3′) and the reverse primer Ser16S-R (5'-TA AGG TTC TTC GCG TTGCAT-3′) after 5 days. The insect midgut was dissected, and total DNA was extracted from individual midguts with Lysis buffer containing Tris-HCl, EDTA Nonidet P-40 and proteinase K as described previously (Shan & Liu, 2021). The resulting PCR product's size and quality were confirmed using 1% agarose gel electrophoresis.…”
Section: The Bacterial Strain Colonization In Riptortus Pedestris Midgutmentioning
confidence: 99%